Oral History Interview: John Kutzbach (0753) - Lange, Robert; Kutzbach, John (My University, 2016)
Abstract: Childhood and early education in Reedsburg, WI; The influence of family and teachers; Undergraduate education at the University of Wisconsin in the 1950s; Air Force ROTC training; Completion of a Master’s Degree at UW; Service as an Air Force weather forecaster in France; Return to UW to complete a Ph.D.; Graduate student life and influential mentors at UW; Joining the UW faculty in 1966; Student protest era; Research agenda at UW; Teaching; Service on department committees and as Chair of department; Collaborative research with national and international organizations; Awards and Honors; Legacy as a mentor of young scientists; UW administration; UW students; Global warming.
Interviewed by Robert Lange
Keywords: Research; Institute for Environmental Studies; global warming; climate change; Reedsburg, WI; Center for Climatic Research; Atmospheric and Oceanic Sciences